LE VOLONTARISME CONTRACTUEL À L’ÉPREUVE DU SMART CONTRACT - MANGIN, Céline (Journal international de bioéthique et d’éthique des sciences, 2025)
Smart contracts, which are computer programmes that run automatically when pre-pro grammed conditions are met, will impact the contractual process, especially when their development focuses on the contract formation phase. The use of digital oracles, which transmit information from the real world to the digital world, to trigger the application of the smart contract may degrade the quality of consent, replacing it with mere assent.